Antecedents and consequences of healthiness in café service: Moderating effect of health concern - Song, Myungkeun; Lee, Won Seok; Moon, Joonho (Frontiers in Sustainable Food Systems, 2022)
This study aims to examine the antecedents of consequences of healthiness in the café business context. Additionally, this study attests to the moderating effect of one's concern for health (health concern) between healthiness and attitude. To attain a more vivid response, this research selected Starbucks coffeehouse as a case study. Hygiene, healthiness, and nutritional disclosure are the determinants of healthiness in the café business area. The consequences of healthiness are attitude and purchase intention for café products. Health concern is the moderating variable between healthiness and attitude in the context of café businesses. In order to test the association between attributes, a survey was used. Amazon Mechanical Turk was chosen to recruit survey participants. The valid observation for data analysis was 455 participants. For hypothesis testing, a structural equation model was implemented. Regarding the results, health concern is positively influenced by hygiene and organicness, but healthiness is negatively affected by nutritional disclosure. Moreover, it was found that health concern significantly moderates the relationship between healthiness and attitude, and attitude exerts a positive effect on purchase intention.